Influencia del acompañamiento familiar en el uso de dispositivos digitales en niños de cinco años de la Institución Educativa Inicial N° 548 Mi Mundo Infantil, Iquitos, 2021 - Torres Cordova, Claudia Alexandra (2022)
The present investigation seeks to determine the influence of family accompaniment on the use of digital devices by five-year-old children from the initial educational institution N° 548 "My Children's World ", Iquitos, 2021. The type of research was descriptive and the non-experimental and correlational design with a quantitative approach. The technique used for this study was the survey, the instrument used was the questionnaire. The results of this study were carried out based on a total sample of N=160 parents of 5-year-old students of the I.E.I. N° 548 "My Children's World". The results of the research indicate that 81.3% (n=130) of parents tend to have agreements on the proper use of digital devices, where the mother is the most participative in the child's education, setting standards and rules, having a 54.5% (n=71) participation. Normally the sustained agreements are the content that the child can view, a norm that 34.6% (n=45) of the parents apply. 60.0% of parents who answered the questionnaire accompany and guide their children when they use digital devices, always guiding them in virtual classes and in the different uses they give them. So, we can conclude that family accompaniment significantly influences the use of digital devices by five-year-old children from the initial educational institution N° 548 "My Children's World", Iquitos, 2021.